Celebrity Compilers - Campbell, Bill; Iyer, Swami; Akbal-Delibas, Bahar (Introduction to Compiler Construction in a Java World, 2013)
Here we survey some of the popular Java (or Java-like) compilers. For each of these, we discuss issues or features that are peculiar to the compiler in question. The compilers we discuss are the following:• Oracle’s Java HotSpotTM compiler • IBM’s Eclipse compiler for Java • The GNU Java compiler • Microsoft’s C# compilerThis chapter will only give a taste of these compilers. The reader may wish to consult some of the recommended readings in the Further Readings section (Section 8.6) at the end of this chapter for a deeper understanding of them.